2009
DOI: 10.1111/j.1460-9568.2009.06990.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute action of rotenone on nigral dopaminergic neurons – involvement of reactive oxygen species and disruption of Ca2+ homeostasis

Abstract: Rotenone is a toxin used to generate animal models of Parkinson's disease; however, the mechanisms of toxicity in substantia nigra pars compacta (SNc) neurons have not been well characterized. We have investigated rotenone (0.05-1 microm) effects on SNc neurons in acute rat midbrain slices, using whole-cell patch-clamp recording combined with microfluorometry. Rotenone evoked a tolbutamide-sensitive outward current (94 +/- 15 pA) associated with increases in intracellular [Ca(2+)] ([Ca(2+)](i)) (73.8 +/- 7.7 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
67
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 70 publications
(156 reference statements)
1
67
0
1
Order By: Relevance
“…Endogenous H 2 O 2 is formed upon mitochondrial dysfunction 9 and elicited by rotenone administration. 21 It can also be amplified by irreversible inhibition of peroxidase enzymes, and can lead to K ATP channel opening and suppression of axonal DA release. 22 Furthermore, in vivo studies investigating acute exposure to rotenone have shown increased generation of ROS during DA metabolism in nigrostriatal neurons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous H 2 O 2 is formed upon mitochondrial dysfunction 9 and elicited by rotenone administration. 21 It can also be amplified by irreversible inhibition of peroxidase enzymes, and can lead to K ATP channel opening and suppression of axonal DA release. 22 Furthermore, in vivo studies investigating acute exposure to rotenone have shown increased generation of ROS during DA metabolism in nigrostriatal neurons.…”
mentioning
confidence: 99%
“…22 Furthermore, in vivo studies investigating acute exposure to rotenone have shown increased generation of ROS during DA metabolism in nigrostriatal neurons. 21 32 In this work, the carbon-fiber electrode was positioned in the dorsal striatum of an anesthetized rat and ramped from −0.4 to 1.4 V in a triangular waveform every 100 ms at a scan rate of 400 V/s. This produces a large and stable nonfaradaic background current that can be subtracted to reveal smaller faradaic currents produced by electroactive analytes in the immediate vicinity of the electrode.…”
mentioning
confidence: 99%
“…Fenamates like FFA are antiinflammatory drugs known to alter ion fluxes through the plasma membrane. They are for instance, potent blockers of cation and anion channels, and FFA at ≥50 μM is now commonly used to block currents through TRP channels and receptor-operated channels (40). Previous experiments have shown that tonic activation of TRP channels maintains basal firing rate, as well as the regularity of firing, in SNr neurons (47).…”
Section: Catalase and Trp Channels In Substantia Nigra And Parkinson'mentioning
confidence: 99%
“…Rotenone decreases intracellular ATP levels and increases the production of ROS including superoxide anion, H 2 O 2 and singlet oxygen (39). It also releases glutamate presynaptic terminals, leading to an additional increase in ROS production (40). Mitochondrial derived ROS can also activate TRPM2 channels (32).…”
Section: Catalase and Trp Channels In Substantia Nigra And Parkinson'mentioning
confidence: 99%
See 1 more Smart Citation